2012
DOI: 10.1177/0892705712458445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polymeric matrix melt flow index in reprocessing extruded wood–plastic composites

Abstract: This article presents an experimental study on the effect of polymeric matrix flow behavior on the properties of the reprocessed wood-plastic composites (WPC) of highdensity polyethylene (HDPE) and wood sawdust. WPCs are considered as sustainable materials due to their durability in the environmental conditions and recyclability. Three grades of HDPE were utilized as polymeric matrix with different melt flow indices (MFIs). Composites containing 60 wt% of sawdust were manufactured via a twin-screw extruder to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 27 publications
0
12
2
Order By: Relevance
“…Even so that reprocessing or recyclability of WPC is still a minor subject in research [21], hitherto, several studies revealed that the issues has gained more interest in terms of scarcity of resources, mechanical and thermal degradation and particle degradation within lignocellulosic particle/fibre composites [32,33,[69][70][71][72][73][74][75][76][77][78]. Repeated reprocessing usually results in reduced mechanical properties [32,70,71], several studies revealed initially increased mechanical properties after reprocessing wood/polypropylene composites [32,34,76,79].…”
Section: Reprocessing Of Wpcmentioning
confidence: 99%
“…Even so that reprocessing or recyclability of WPC is still a minor subject in research [21], hitherto, several studies revealed that the issues has gained more interest in terms of scarcity of resources, mechanical and thermal degradation and particle degradation within lignocellulosic particle/fibre composites [32,33,[69][70][71][72][73][74][75][76][77][78]. Repeated reprocessing usually results in reduced mechanical properties [32,70,71], several studies revealed initially increased mechanical properties after reprocessing wood/polypropylene composites [32,34,76,79].…”
Section: Reprocessing Of Wpcmentioning
confidence: 99%
“…This can be attributed to the encapsulation of NaCl crystals using a thermoplastic similar to other fillers: composites such as NaCl/PS/CNT possess less than the minimum NaCl content to form a continuous network throughout the composite to leach NaCl using water. 31,43 Water penetration into the composites and the dissolution of the NaCl crystals, that is, leaching of NaCl, were easier in composites with higher NaCl contents, because there were more possible paths for the solvent to seep through the NaCl network. This is why voids were not only observable on the surface of the samples but also in the crosssections of the samples.…”
Section: Morphologymentioning
confidence: 99%
“…Additionally, it has been reported that melt flow index (MFI) of WPCs shows great importance for the relationship between structure‐property. Sarabi et al 25 investigated the effect of reprocessing and MFI of high density polyethylene (HDPE) on the mechanical and physical properties of WPC. Composites with low‐MFI HDPE indicated the lowest water absorption and higher flexural and tensile properties among virgin composites, whereas for the reprocessed ones, higher water absorption was verified for composites with low MFI; upon increasing MFI composites became weaker under flexural and tensile loads.…”
Section: Introductionmentioning
confidence: 99%